A Study on transformational leadership - Kim, Young Jun (KDI School, 1998)
Transformational leadership was formulated in the 1980s as an alternative leadership paradigm to meet the needs of the new era. This thesis examines the essential characteristics of transformational leadership through review of the existing literature and case studies of 10 representative CEOs Based on the1 0 case studies, the author found four common behavioral characteristics of transformational leadership such as idealized influence, inspirational motivation, intellectual stimulation and individualized consideration. In addition, transformational leaders were skilled at forming human network, had good insights and intuition to see the future, had talents in taking symbolic actions for the turnaround and for moving forward to realize the vision of their corporations.
Thesis(Master) --KDI School:Master of Strategy & International Management,1998